The Maestros Voyage Documentary Special Screening reveals historical treasures - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 17 January 2023 - Universiti Malaysia Pahang (UMP) organised a Documentary Special Screening (The Maestro’s Voyage) and Scholar Dialogue Session that revealed the history of the Malay empire starting in Melaka as a rapid international trading port and a centre for education, economy, propagation of Islam and Malay arts.